Monetary expansion in Britain in the late twelfth century - Crafter, TCR (2007)
The thesis is conceived as a contribution to the quantification of the monetary expansion that occurred in Britain c.1150-c.1200. The increased money supply facilitated developments in commerce and was connected with increasing population and urbanisation. Changes in the monetary system and the source of bullion are examined. This thesis draws upon a range of previously unpublished numismatic material that is collated and catalogued for the first time,and which is subjected to analytical techniques. It is known that monetary expansion occurrence large scale in the thirteenth century and iris here suggested that the increase began on comparatively modest scale in England during the Cross and Cross lets coinage (1158-1180) and in Scotland during the Crescents coinage (c.1170-1195). The English coinage is considered through primary evidence of a die-study of the Northampton mint and the content of the Gayton hoard (1998-9) in conjunction and comparison with other published information. The Scottish coinage is subjected to comprehensive investigation by die-study to provide the first analysis of the structure and internal chronology of the coinage, which is prerequisite to understanding the extent of the monetary expansion. The thesis provides the first investigation of the alloy of late twelfth-century coins using Electron Probe Microanalysis (ELMA). The data demonstrates that alloy content varied by region and that the contribution of bullion from the ‘mine of Carlisle’ had only a peripheral influence on monetary expansion. EPMA data is compared with evidence from the Dialogus de Scaccario. Metallurgical analysis indicates that monetary expansion occurred in Scotland in the late twelfth century when coinage, functioning as a standardised means of exchange,became more useful than wealth stored in stocks of bullion; it was not specifically caused by a local argentiferous discovery. Trace elements in the alloy of Scottish coins indicate that some bullion utilised for coinage had been in Scotland since the Viking Age, and had originated from Samanid Central Asia.